Deficiency of Gpr1 improves steroid hormone abnormality in hyperandrogenized mice - Ya-Li Yang; Li-Feng Sun; Yan Yu; Tian-Xia Xiao; Bao-Bei Wang; Pei-Gen Ren; Hui-Ru Tang; Jian V. Zhang (BMC, 2018)
Abstract Background Polycystic ovary syndrome (PCOS) is a complex genetic disease with multifarious phenotypes. Many researches use dehydroepiandrosterone (DHEA) to induce PCOS in pubertal mouse models. The aim of this study was to investigate the role of GPR1 in dehydroepiandrosterone (DHEA)-induced hyperandrogenized mice. Methods Prepubertal C57BL/6 mice (25 days of age) and Gpr1-deficient mice were each divided into two groups and injected daily with sesame oil with or without DHEA (6 mg/100 g) for 21 consecutive days. Hematoxylin and eosin (H&E) staining was performed to determine the characteristics of the DHEA-treated ovaries. Real-time PCR was used to examine steroid synthesis enzymes gene expression. Granulosa cell was cultured to explore the mechanism of DHEA-induced, GPR1-mediated estradiol secretion. Results DHEA treatment induced some aspects of PCOS in wild-type mice, such as increased body weight, elevated serum testosterone, increased number of small, cystic, atretic follicles, and absence of corpus luteum in ovaries. However, Gpr1 deficiency significantly attenuated the DHEA-induced weight gain and ovarian phenotype, improving steroidogenesis in ovaries and estradiol synthesis in cultured granulosa cells, partially through mTOR signaling. Conclusions In conclusion, Gpr1 deficiency leads to the improvement of steroid synthesis in mice hyperandrogenized with DHEA, indicating that GPR1 may be a therapeutic target for DHEA-induced hyperandrogenism.